VD_FINDINFO AI 53/09 - 45/2011 vom 28. Januar 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, RECONSIDÉRATION, FORCE PROBANTE, RAPPORT MÉDICAL | 28 LAI, 4 LAI, 69 al. 1bis LAI, 83 LOJV, 16 LPGA, 38 LPGA, 53 al. 2 LPGA, 6 LPGA, 60 al. 1 LPGA, 61 let. b LPGA, 61 let. g LPGA, 7 LPGA, 8 al. 1 LPGA, 88bis al. 2 let. a RAI, 117 al. 1 LPA-VD, 2 al. 1 let. c LPA-VD, 49 al. 1 LPA-VD, 55 al. 1 LPA-VD, 79 LPA-VD, 91 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD, 99 LPA-VD